PREVENTIVE PURPOSE OF QUERCETIN FOR CORONAVIRUS INFECTION IN MEDICAL WORKERS (Academicia Globe: Inderscience Research, 2023)
Patients with metabolic disorders and chronic diseases are most susceptible to SARS-CoV-2. Among the possible factors of organ damage, systemic hyperimmune inflammation due to the "cytokine storm", cytopathic effects, hypoxia, and drug toxicity are considered. This study indicates the effective results of using the drug quertin and its combination with ascorbic acid on the incidence rates of the healthcare sector working with patients with COVID-19.